2023
DOI: 10.1002/ptr.7853
|View full text |Cite
|
Sign up to set email alerts
|

Lonicerin alleviates the progression of experimental rheumatoid arthritis by downregulating M1 macrophages through the NF‐κB signaling pathway

Abstract: The present study aimed to evaluate anti‐rheumatoid arthritis (RA) effect of Lonicerin (LON), a safe compound with anti‐inflammatory and immunomodulatory properties. Nevertheless, the exact role of LON in RA remains elusive. In this test, the anti‐RA effect of LON was evaluated in collagen‐induced arthritis (CIA) mouse model. Relevant parameters were measured during the experiment; ankle tissue and serum were collected at the end of the experiment for radiology, histopathology, and inflammation analysis. ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…NLRP3 inflammasome activation is the key molecular event in M1 macrophage polarization releasing pro-inflammatory cytokines. For instance, LPS promoted M1-type macrophage polarization to promote NLRP3 inflammasome formation to release pro-inflammatory cytokines IL-1β and IL-18 . SIRT1 overexpression would decrease endogenous LPS production and inhibit macrophagic NLRP3 inflammasome formation to suppress NF-κB-induced inflammation, which together to alleviate hepatic inflammatory injury and fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome activation is the key molecular event in M1 macrophage polarization releasing pro-inflammatory cytokines. For instance, LPS promoted M1-type macrophage polarization to promote NLRP3 inflammasome formation to release pro-inflammatory cytokines IL-1β and IL-18 . SIRT1 overexpression would decrease endogenous LPS production and inhibit macrophagic NLRP3 inflammasome formation to suppress NF-κB-induced inflammation, which together to alleviate hepatic inflammatory injury and fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in another study using Lonicerin as a therapeutic compound. In vivo and in vitro studies revealed that Lonicerin significantly decreased M1 marker levels by attenuating the activation of the NF-κB signalling pathway, which contributes to M1 macrophage polarization and inflammasome activation ( Yang et al, 2023 ).…”
Section: Functions Of Macrophage Polarization In Rheumatoid Arthritismentioning
confidence: 99%
“…and regulates oxidative stress, and immunity. The progress of 2,4,6-trinitrobenzene sulfonic acid-induced ulcerative colitis, candida albicans-caused arthritis and collagen-induced arthritis was suppressed by lonicerin via reducing inflammatory response [ 15 , 16 , 17 ]. EZH2 and NF-κB were targeted by lonicerin, separately, and then apoptosis and inflammation were reduced [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%